A method for recovering and preparing battery-grade iron phosphate from iron phosphorus slag based on ultrasonic-induced crystallization
Patent Information
- Application Number
- CN202411512318.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-10-28
AI Technical Summary
[0004]中国专利CN 112520718 A公开了一种从铁磷渣酸浸液中选择性回收电池级磷酸铁的方法,即用无机酸浸出铁磷渣,再加入碱性沉淀剂选择性沉淀磷酸铁,同时去除杂质金属元素,这一方法存在着消耗碱性沉淀剂,沉淀母液难以处理的问题
[0018] (1) Ultrasonic assistance is used in the crystallization process. The cavitation effect of ultrasound enhances the nucleation process of solution crystallization and improves the crystallization rate of the crystallized product at low supersaturation concentration. This not only avoids the use of alkaline precipitants from the source and reduces the discharge of alkaline wastewater, but also reduces the volume of deionized water added to the leachate during the crystallization process, so that the concentrated crystallization mother liquor can be returned to the leaching process for recycling.
Abstract
Description
Technical Field
[0001] This invention relates to a method for recovering and preparing battery-grade iron phosphate from iron-phosphorus slag based on ultrasonic-induced crystallization, and particularly to a method for resource recovery and high-value utilization of iron and phosphorus in iron-phosphorus slag based on an "inorganic acid leaching-ultrasonic-induced crystallization-high-temperature dehydration" process, belonging to the fields of waste lithium-ion battery recycling and metallurgical environmental engineering. Background Technology
[0002] Lithium iron phosphate (LFP) batteries possess advantages such as high theoretical capacity, low cost, non-toxicity, good charge-discharge reversibility, and high stability, making them a promising cathode material for lithium-ion batteries and holding a significant share in the new energy vehicle and energy storage industries. However, as LFP batteries reach the end of their lifespan, their number of retired batteries is bound to surge. From both resource and environmental perspectives, the recycling and reuse of retired LFP batteries is urgently needed.
[0003] Lithium is the most valuable element in retired lithium iron phosphate batteries, and its recovery is crucial for improving economic efficiency. The selective recovery of lithium from lithium iron phosphate-containing battery waste via oxidative leaching is a mature and industrialized process. However, the iron-phosphorus slag produced by oxidative leaching faces the challenge of high-value utilization due to its poor economic viability. Therefore, there is an urgent need to develop efficient and clean recovery processes for iron and phosphorus resources in iron-phosphorus slag to achieve its resource utilization.
[0004] Chinese patent CN 112520718 A discloses a method for selectively recovering battery-grade iron phosphate from iron-phosphorus slag acid leaching solution. This method involves leaching the iron-phosphorus slag with inorganic acid, then adding an alkaline precipitant to selectively precipitate iron phosphate while simultaneously removing impurity metal elements. However, this method suffers from the problem of consuming alkaline precipitant and the difficulty in treating the mother liquor. Chinese patent CN113044824 A discloses a method for recycling iron phosphate waste. This method uses a small portion of the iron-phosphorus solution to prepare an iron phosphate precipitant, which is then added to the remaining iron-phosphorus solution to react and obtain dihydrate iron phosphate precipitate. A portion of the dihydrate iron phosphate precipitate is retained as a precipitant for subsequent batches, while the remaining dihydrate iron phosphate precipitate is used to produce anhydrous iron phosphate. This method only requires alkaline solution in the precipitant preparation stage, reducing the consumption of alkaline precipitant and making it more environmentally friendly. However, the process is complex and requires sophisticated production equipment.
[0005] Existing technologies for preparing battery-grade iron phosphate from recycled iron-phosphate slag mostly suffer from problems such as high reagent consumption, large washing water volume, and difficulty in treating saline wastewater. Therefore, reducing reagent consumption and saline wastewater generation, decreasing washing water volume, and improving the quality of iron phosphate products are urgent issues that need to be addressed. Summary of the Invention
[0006] The purpose of this invention is to provide a method for recovering and preparing battery-grade iron phosphate from iron-phosphorus slag based on ultrasonic-induced crystallization. This method uses inorganic acid to leach the iron-phosphorus slag, adjusts the pH by diluting with a small amount of water, and induces crystallization using ultrasound, thereby reducing the amount of acid and alkali used and wastewater generated. This achieves low-cost resource recovery and high-value utilization of iron and phosphorus elements in the iron-phosphorus slag. This method has advantages such as low reagent consumption, recyclable solution system, and low wastewater discharge, providing a new approach for iron-phosphorus slag recovery and showing good application prospects.
[0007] To achieve the above objectives, the specific steps of the method are as follows:
[0008] (1) The iron-phosphorus slag was leached with inorganic acid. After the reaction was completed, the residue was filtered to obtain a leachate containing iron and phosphorus.
[0009] (2) A certain amount of deionized water is added to the leachate for dilution, and then the temperature is increased and a crystallization reaction is carried out with the assistance of ultrasound.
[0010] (3) After the crystallization reaction is complete, the precipitate of ferric phosphate dihydrate and the mother liquor of crystallization are obtained by filtration. The mother liquor of crystallization is concentrated and returned to step (1) for recycling. The ferric phosphate dihydrate is thoroughly washed to remove impurities. The wash water is returned to step (2) as dilution water and then dehydrated at high temperature to obtain battery-grade anhydrous ferric phosphate.
[0011] Further, the iron-phosphorus slag mentioned in step (1) is one or more of the following: lithium iron phosphate waste after lithium extraction from lithium iron phosphate waste, lithium iron phosphate waste after lithium extraction from lithium iron phosphate electrode recycling, lithium iron phosphate waste after lithium extraction from dismantled retired lithium iron phosphate batteries, or lithium iron phosphate waste after lithium extraction from mixed black powder of positive and negative electrodes of retired lithium iron phosphate batteries, wherein the mass fraction of Fe element is 15~30% and the mass fraction of P element is 13~20%.
[0012] Furthermore, the inorganic acid used in the leaching process in step (1) is one or more of hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, the concentration of inorganic acid is 1~8 mol / L, the liquid-to-solid ratio is 2~10 mL / g, the leaching temperature is 25~65 ℃, and the leaching time is 30~240 min.
[0013] Furthermore, in step (2), the volume of deionized water added is 0.2 to 2 times the volume of the leachate. If too much deionized water is added, the subsequent concentration of the mother liquor for crystallization will be large and the energy consumption will be high; if too little deionized water is added, the pH of the solution will be low at the beginning of crystallization, making it difficult for ferric phosphate to crystallize.
[0014] Furthermore, in step (2), the pH of the crystallization process is controlled at 0.5~1.2, the temperature at 75~200 ℃, and the time at 20~240 min. If the pH of the crystallization process is too high, sufficient deionized water needs to be added, making it difficult to concentrate the mother liquor in the subsequent crystallization process; if the pH is too low, the solubility of ferric phosphate dihydrate will increase, which is not conducive to crystallization.
[0015] Furthermore, in step (2), the ultrasonic frequency used to assist crystallization is 20~60 kHz, and the ultrasonic power is 20~100 W. If the ultrasonic frequency is too high, it will make the system unstable and damage the crystal structure; if the frequency is too low, it will not be able to effectively stimulate the nucleation process and affect the crystallization rate. If the ultrasonic power is too high, it will increase energy consumption and even cause the solution temperature to rise; if the power is too low, it will lead to a decrease in the number of nuclei and a slower crystallization rate. In general, if the ultrasonic frequency / power is too high, it will affect the crystal quality; if it is too low, it will affect the crystallization efficiency.
[0016] Furthermore, the mother liquor from the crystallization in step (3) is concentrated to the volume of the inorganic acid leaching agent in step (1) and then returned to step (1) for recycling as a leaching agent.
[0017] The present invention provides a method for preparing battery-grade iron phosphate from iron-phosphorus slag based on ultrasonic-induced crystallization, which has the following advantages compared with the prior art:
[0018] (1) Ultrasonic assistance is used in the crystallization process. The cavitation effect of ultrasound enhances the nucleation process of solution crystallization and improves the crystallization rate of the crystallized product at low supersaturation concentration. This not only avoids the use of alkaline precipitants from the source and reduces the discharge of alkaline wastewater, but also reduces the volume of deionized water added to the leachate during the crystallization process, so that the concentrated crystallization mother liquor can be returned to the leaching process for recycling.
[0019] (2) Ultrasonic-assisted crystallization was used to refine the grains by utilizing the dispersing effect of ultrasound, thereby improving the particle size and specific surface area of the crystalline product of iron phosphate dihydrate, and realizing the control of the physical properties of battery-grade iron phosphate from the precursor. Detailed Implementation
[0020] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with specific embodiments.
[0021] Example 1
[0022] The iron-phosphorus slag from lithium iron phosphate waste, containing 24.43% Fe and 12.50% P by mass, was leached with 3.5 mol / L phosphoric acid at a liquid-to-solid ratio of 5 mL / g at 65 ℃ for 240 min. After filtration, the leachate yielded iron and phosphorus leaching rates of 98.84% and 98.69%, respectively. The leachate was then mixed with 100 ml of deionized water and subjected to ultrasonic treatment at 70 ℃ for 150 min at a frequency of 40 kHz and a power of 80 W. Filtration yielded ferric phosphate dihydrate precipitate with a crystallization rate of 84.7%. The ferric phosphate dihydrate product was washed, dried, and calcined to obtain anhydrous ferric phosphate.
[0023] Characterization showed that the anhydrous iron phosphate had an iron-to-phosphorus molar ratio of 0.977 and a particle size (D) of [missing information]. 50 The micrometer diameter (μm) is 8.96 μm, and the specific surface area is 4.04 m². 2 / g. The lithium iron phosphate cathode material prepared using this anhydrous iron phosphate as a precursor exhibits a discharge specific capacity of 158.8 mAh / g at 0.1C, and after 100 cycles at 1C, the capacity retention rate is 99.2%, meeting battery-grade standards. The concentrated crystallization mother liquor is returned to the leaching process for recycling. After three cycles, the iron and phosphorus leaching rates, the crystallization rate of iron phosphate dihydrate, and the quality of the iron phosphate product all remain stable.
[0024] Example 2
[0025] The iron-phosphorus residue from the extraction of lithium from the positive and negative electrodes of retired lithium iron phosphate batteries, containing 28.96% Fe and 18.33% P by mass, was leached with 8 mol / L phosphoric acid at a liquid-to-solid ratio of 10 mL / g at 45℃ for 60 min. After filtration, the leachate yielded iron and phosphorus leaching rates of 97.96% and 98.01%, respectively. Subsequently, 100 ml of the leachate was mixed with 200 ml of deionized water and subjected to ultrasonic treatment at 20 kHz and 60 W for 60 min at 200℃. Filtration yielded iron phosphate dihydrate precipitate with a crystallization rate of 91.9%. The iron phosphate dihydrate product was washed, dried, and calcined to obtain anhydrous iron phosphate.
[0026] Characterization showed that the anhydrous iron phosphate had an iron-to-phosphorus molar ratio of 0.970 and a particle size (D) of... 50 The micrometer diameter (μm) is 8.57 μm, and the specific surface area is 3.38 m². 2 / g. The lithium iron phosphate cathode material prepared using this anhydrous iron phosphate as a precursor exhibits a discharge specific capacity of 158.2 mAh / g at 0.1C, and after 100 cycles at 1C, the capacity retention rate is 98.8%, meeting battery-grade standards. The concentrated crystallization mother liquor is returned to the leaching process for recycling. After three cycles, the iron and phosphorus leaching rates, the crystallization rate of iron phosphate dihydrate, and the quality of the iron phosphate product all remain stable.
[0027] Example 3
[0028] Iron-phosphorus slag from the dismantling and lithium extraction of retired lithium iron phosphate batteries, containing 17.53% Fe and 13.29% P by mass, was leached with 2 mol / L sulfuric acid at a liquid-to-solid ratio of 3 mL / g at 25 °C for 180 min. The leachate was filtered, yielding iron and phosphorus leaching rates of 98.05% and 98.44%, respectively. Subsequently, 100 ml of the leachate was mixed with 200 ml of deionized water and subjected to ultrasonic treatment at 100 °C for 240 min at a frequency of 60 kHz and a power of 100 W. The mixture was then filtered to obtain iron phosphate dihydrate precipitate with a crystallization rate of 90.4%. The iron phosphate dihydrate product was washed, dried, and calcined to obtain anhydrous iron phosphate.
[0029] Characterization showed that the anhydrous iron phosphate had an iron-to-phosphorus molar ratio of 0.965 and a particle size (D) of [missing information]. 50 Its thickness is 7.55 μm, and its specific surface area is 4.04 m². 2 / g. The lithium iron phosphate cathode material prepared using this anhydrous iron phosphate as a precursor exhibits a discharge specific capacity of 160.1 mAh / g at 0.1C, and after 100 cycles at 1C, the capacity retention rate is 99.4%, meeting battery-grade standards. The concentrated crystallization mother liquor is returned to the leaching process for recycling. After three cycles, the iron and phosphorus leaching rates, the crystallization rate of dihydrate iron phosphate, and the quality of the iron phosphate product all remain stable.
[0030] Example 4
[0031] The iron-phosphorus residue from lithium iron phosphate electrode recovery, containing 25.93% Fe and 17.36% P by mass, was leached with 4 mol / L hydrochloric acid at a liquid-to-solid ratio of 5 mL / g at 40 °C for 120 min. The leachate was filtered, yielding iron and phosphorus leaching rates of 98.49% and 98.98%, respectively. 100 ml of the leachate was then mixed with 80 ml of deionized water and subjected to ultrasonic treatment at 45 kHz and 75 W at 90 °C for 90 min. Fiber phosphate dihydrate precipitate was obtained by filtration, with a crystallization rate of 89.5%. The ferric phosphate dihydrate product was washed, dried, and calcined to obtain anhydrous ferric phosphate.
[0032] Characterization showed that the anhydrous iron phosphate had an iron-to-phosphorus molar ratio of 0.968 and a particle size (D) of... 50 The micrometer diameter (μm) is 5.90 μm, and the specific surface area is 5.85 m². 2 / g. The lithium iron phosphate cathode material prepared using this anhydrous iron phosphate as a precursor exhibits a discharge specific capacity of 159.6 mAh / g at 0.1C, and after 100 cycles at 1C, the capacity retention rate is 99.5%, meeting battery-grade standards. The concentrated crystallization mother liquor is returned to the leaching process for recycling. After three cycles, the iron and phosphorus leaching rates, the crystallization rate of iron phosphate dihydrate, and the quality of the iron phosphate product all remain stable.
[0033] Comparative Example 1
[0034] The raw materials and experimental procedures were the same as in Example 1, except that after mixing 100 ml each of the leachate and deionized water, ultrasonic assistance was not used. The mixture was kept at 70 °C for 150 min, and then filtered to obtain ferric phosphate dihydrate precipitate with a crystallization rate of 19.4%. The ferric phosphate dihydrate product was washed, dried, and calcined to obtain anhydrous ferric phosphate.
[0035] Characterization showed that the anhydrous iron phosphate had an iron-to-phosphorus molar ratio of 0.964 and a particle size (D) of [missing information]. 50 Its diameter is 23.40 μm, and its specific surface area is 1.18 m². 2 / g. The lithium iron phosphate cathode material prepared using this anhydrous iron phosphate as a precursor exhibits a discharge specific capacity of 139.3 mAh / g at 0.1C, and retains 90.7% of its capacity after 100 cycles at 1C. Compared with Example 1, Comparative Example 1 shows a significant decrease in the crystallinity of iron phosphate dihydrate. This indicates that the cavitation effect of ultrasound enhances the nucleation process of solution crystallization, thereby increasing the crystallinity of the crystalline product at low supersaturation concentrations.
[0036] Comparative Example 2
[0037] The raw materials and experimental procedures were the same as in Example 1, except that the ultrasonic frequency used was 15 kHz and the power was 15 W. The mixture was kept at 70 ℃ for 150 min, and then filtered to obtain ferric phosphate dihydrate precipitate with a crystallization rate of 30.5%. The ferric phosphate dihydrate product was washed, dried, and then calcined to obtain anhydrous ferric phosphate.
[0038] Characterization showed that the anhydrous iron phosphate had an iron-to-phosphorus molar ratio of 0.969 and a particle size (D) of... 50 The micrometer diameter (μm) is 16.96 μm, and the specific surface area is 1.98 m². 2 / g. The lithium iron phosphate cathode material prepared using this anhydrous iron phosphate as a precursor exhibits a discharge specific capacity of 142.5 mAh / g at 0.1C and retains 98.4% of its capacity after 100 cycles at 1C. Comparative Example 2 shows a lower crystallinity of iron phosphate dihydrate compared to Example 1. This indicates that excessively low ultrasonic frequency and power can hinder the effective activation of the nucleation process, thus affecting the crystallinity.
[0039] Comparative Example 3
[0040] The raw materials and experimental procedures were the same as in Example 1, except that the ultrasonic frequency used was 70 kHz and the power was 110 W. The temperature was maintained at 70 ℃ for 150 min, and the precipitate of ferric phosphate dihydrate was obtained by filtration, with a crystallization rate of 89.1%. The ferric phosphate dihydrate product was washed, dried, and calcined to obtain anhydrous ferric phosphate.
[0041] Characterization showed that the anhydrous iron phosphate had an iron-to-phosphorus molar ratio of 0.967 and a particle size (D) of [missing information]. 50 The micrometer diameter (μm) is 6.39 μm, and the specific surface area is 4.07 m². 2 / g. The lithium iron phosphate cathode material prepared using this anhydrous iron phosphate as a precursor exhibits a discharge specific capacity of 155.8 mAh / g at 0.1C, and retains 85.7% of its capacity after 100 cycles at 1C. Compared to Example 1, Comparative Example 3 shows a slightly lower crystallinity of iron phosphate dihydrate. This indicates that excessively high ultrasonic power and frequency do not lead to a sustained increase in crystallinity, but rather increase energy consumption. Furthermore, excessive ultrasonication can damage the material structure, affecting the electrochemical cycling performance of the synthesized material.
[0042] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for recovering and preparing battery-grade iron phosphate from iron-phosphorus slag based on ultrasonic-induced crystallization, characterized in that, The steps of the method are as follows: (1) The iron-phosphorus slag was leached with inorganic acid. After the reaction was completed, the residue was filtered to obtain a leachate containing iron and phosphorus. (2) Add deionized water to the leachate for dilution, then raise the temperature and carry out a crystallization reaction with the assistance of ultrasound; (3) After the crystallization reaction is completed, the precipitate of ferric phosphate dihydrate and the mother liquor of crystallization are obtained by filtration. The volume of the mother liquor of crystallization is concentrated to the volume of the inorganic acid leaching agent in step (1), and then returned to step (1) as a leaching agent for recycling. The ferric phosphate dihydrate is thoroughly washed to remove the impurities. The wash water is returned to step (2) as dilution water, and then dehydrated at high temperature to obtain battery-grade anhydrous ferric phosphate. The iron-phosphorus slag mentioned in step (1) is one or more of the following: lithium iron phosphate waste after lithium extraction from lithium iron phosphate waste, lithium iron phosphate waste after lithium extraction from lithium iron phosphate electrode recycling, lithium iron phosphate waste after lithium extraction from dismantled retired lithium iron phosphate batteries, or lithium iron phosphate waste after lithium extraction from mixed black powder of positive and negative electrodes of retired lithium iron phosphate batteries; the mass fraction of Fe element in the iron-phosphorus slag is 15%~30%, and the mass fraction of P element is 13%~20%; In step (2), the ultrasonic frequency used to assist crystallization is 20~60kHz, the ultrasonic power is 20~100W, the pH of the crystallization process is controlled at 0.5~1.2, and the temperature is 75~200℃.
2. The method for preparing battery-grade iron phosphate from iron-phosphorus slag based on ultrasonic-induced crystallization according to claim 1, characterized in that, The inorganic acid used in step (1) is one or more of hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid. The concentration of the inorganic acid is 1~8 mol / L, the liquid-to-solid ratio is 2~10 mL / g, the leaching temperature is 25~65℃, and the leaching time is 30~240 min.
3. The method for preparing battery-grade iron phosphate from iron-phosphorus slag based on ultrasonic-induced crystallization according to claim 1, characterized in that, In step (2), the volume of deionized water added is 0.2 to 2 times the volume of the leachate.
4. The method for preparing battery-grade iron phosphate from iron-phosphorus slag based on ultrasonic-induced crystallization according to claim 1, characterized in that, The crystallization process in step (2) takes 20 to 240 minutes.
Citation Information
Patent Citations
Method for selectively recovering battery-grade iron phosphate from lithium extraction residue pickle liquor
CN112520718A
Iron phosphate waste cyclic regeneration method and application thereof
CN113044824A
Method for ultrasonic preparation of nano iron phosphate of lithium iron phosphate
CN104505495A
Method for recovering iron phosphate slag after lithium extraction of battery
CN117069081A